Analisis Pengendalian Persediaan Bahan Baku Pada PT XYZ Dengan Metode Economic Order Quantity Menggunakan Software POM-QM - Harys W. Ramadhan; M. Tutuk Safirin (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
PT XYZ is an industrial company that produces tools. In this research, the problem that must be resolved, namely the issue of raw material inventory control that occurs at PT XYZ, will be resolved using the Economic Order Quantity (EOQ) method using POM-QM software. By using the Economic Order Quantity (EOQ) method, it is hoped that it can solve the raw material inventory control problems that occur at PT XYZ so that the costs incurred by the company are optimal. So, PT XYZ can solve the problem of controlling raw material inventory with the help of the POM-QM application to facilitate the calculation process. Based on the analysis and data processing that has been carried out, it is known that the optimal quantity of raw material A output per order is 150 units with a total cost of IDR 270,596,000 and a reorder point value of 7 units. For raw material B, the optimal quantity per order is 241 units with a total cost of IDR 2,439,490,000 and a reorder point value of 53 units. For raw material C, the optimal quantity per order is 94 units with a total cost of IDR 425,200,400 and a reorder point value of 7 units. For raw material D, the optimal quantity per order is 82 units with a total cost of IDR 217,229,600 and a reorder point value of 5 units. So the raw material that has the most influence in the tool making process at PT XYZ is B because it has the largest reorder point value.